Genome-Wide Analysis of NLR Disease Resistance Genes in an Updated Reference Genome of Barley - Li, Qian; Jiang, Xing-Mei; Shao, Zhu-Qing (Frontiers in Genetics, 2021)
Barley is one of the top ten crop plants in the world. During its whole lifespan, barley is frequently infected by various pathogens. In this study, we performed genome-wide analysis of the largest group of plant disease resistance (R) genes, the nucleotide binding site–leucine-rich repeat receptor (NLR) gene, in an updated barley genome. A total of 468 NLR genes were identified from the improved barley genome, including one RNL subclass and 467 CNL subclass genes. Proteins of 43 barley CNL genes were shown to contain 25 different integrated domains, including WRKY and BED. The NLR gene number identified in this study is much larger than previously reported results in earlier versions of barley genomes, and only slightly fewer than that in the diploid wheat Triticum urartu. Barley Chromosome 7 contains the largest number of 112 NLR genes, which equals to seven times of the number of NLR genes on Chromosome 4. The majority of NLR genes (68%) are located in multigene clusters. Phylogenetic analysis revealed that at least 18 ancestral CNL lineages were presented in the common ancestor of barley, T. urartu and Arabidopsis thaliana. Among them fifteen lineages expanded to 533 sub-lineages prior to the divergence of barley and T. urartu. The barley genome inherited 356 of these sub-lineages and duplicated to the 467 CNL genes detected in this study. Overall, our study provides an updated profile of barley NLR genes, which should serve as a fundamental resource for functional gene mining and molecular breeding of barley.